Phenomenology, Psychopathology and Jaspers: A Conceptual History”, History of Psychiatry (Phenomenology, Humanities and Sciences, 2025)
The paper presents and discusses the texts in which took place the debate occurred in 1913-1914 between Karl Jaspers and Ludwig Binswanger about the “structural method” in psychopathology (K. Jaspers, Allgemeine Psychopathologie, 1913; and “Kausale und ‘verständliche’ Zusammenhänge zwischen Schicksal und Psychose bei der Dementia praecox – Schizophrenie”; L. Binswanger, “Bemerkungen zu der Arbeit Jaspers’ ‘Kausale und verständliche Zusammenhänge zwischen Schicksal und Psychose bei der Dementia praecox (Schizophrenie)”, 1913; and “Psychologische Tagesfragen innerhalb der klinischen Psychiatrie”, 1914). The aim of the paper is to show the different way in which the two authors embrace phenomenology starting from their reception of Freud’s theories at the beginning of the 1910s.